Righteous Content : Black Women's Perspectives of Church and Faith. - Wiggins, Daphne C. (Religion, Race, & Ethnicity., 2004)
Enter most African American congregations and you are likely to see the century-old pattern of a predominantly female audience led by a male pastor. How do we explain the dedication of African American women to the church, particularly when the church's regard for women has been questioned?. Following in the footsteps of Evelyn Brooks Higginbotham's pathbreaking work, Righteous Discontent, Daphne Wiggins takes a contemporary look at the religiosity of black women. Her ethnographic work explores what is behind black women's intense loyalty to the church, bringing to the fore the voices of the.